Metabolomic profile of medicinal plants with anti-RVFV activity. Issue 2 (February 2022) - More, Garland Kgosi; Vervoort, Jacques; Steenkamp, Paul Anton; Prinsloo, Gerhard
Abstract: Twenty medicinal plants with previously established anti-viral activity against a wild-type RVFV were further investigated using bio-chemometric and analytical techniques. The aim being to identify compounds common in plants with anti-RVFV activity, potentially being the major contributors to the anti-viral effect. Proton nuclear magnetic resonance ( 1 H NMR) spectroscopy coupled with multivariate data analysis (MVDA) was applied to characterize metabolite profiles of twenty antiviral medicinal plants. Discrimination and prediction of metabolome data of active anti-RVFV from the less-active samples was assessed using the multivariate statistical models by constructing a robust principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) regression model. Annotation of metabolites in the samples with higher activity were performed by Chenomx software and the compounds confirmed using Ultra-High-Performance Liquid Chromatography-Quadrupole Time-of-Flight Mass Spectrometry (UHPLC-qTOF-MS). Both the PCA and OPLS-DA score plots showed clustering of samples; however, the OPLS-DA plot indicated a clear separation among active and less-active samples. Metabolic biomarkers were screened by p -value < 0.05 and variable importance in the projection (VIP) value >1 and S-plot. Among active samples, the most prominent metabolites putatively identified by NMR include trigonelline, vanillic acid, fumarate, chlorogenic acid, ferulate, and formate. The presence of the compounds were confirmed by UHPLC-qTOF-MS, and two hydroxylated fatty acids were additionally detected indicated by peaks at m/z 293.2116 and m/z 295.2274 13S-Hydroxy-9Z, 11E, 15Z-octadecatrienoic acid and 13-Hydroxy-9Z, 11E-octadecadienoic acid were annotated for the first time in all the antiviral active samples and are considered potential metabolites responsible for the antiviral activity. The study provides a metabolomic profile of anti-RVFV plant extracts and report for the first time the presence of hydroxylated fatty acids 13S-Hydroxy-9Z, 11E, 15Z-octadecatrienoic acid and 13-Hydroxy-9Z, 11E-octadecadienoic acid, present in all the tested medicinal plants with high anti-RVFV activity and is a potential target for the future development of antiviral therapeutic agents. Abstract : 1 H-NMR-metabolomics; UHPLC-qTOF-MS; Medicinal plants; Anti-viral; Rift valley fever virus.